The Process of Performance Based Budgeting in Probolinggo City by Utilizing SIMRAL: A Phenomenology Study - Dipayana, Muhammad Avicinna; Triyuwono, Iwan; Andayani, Wuryan (Journal of Accounting and Business Education, 2017)
This study aims to interpret the performance-based budgeting process by utilizing Planning, Budgeting and Reporting Information System (SIMRAL) in Probolinggo Cityâs budget. This research is regarded as qualitative, particularly referring to phenomenological study projected to dig deep into the informantsâ perspectives and their meaning. The results of this study revealed that the performance-based budgeting process in Probolinggo City with SIMRALâs utilization is interpreted the disobedience of budgeting to planning; moreover, SIMRAL is regarded as a solution for such disobedience. Referring to such a notion, a conclusion can be drawn which reads "SIMRAL is the solution for the disobedience of budgeting to planning". The understanding of the meaning of performance-based budgeting with SIMRALâs utilization did not necessarrily make the Probolinggo municipal government implement the performance-based budgeting in accordance with the rules. The factors leading to such a situasion are outlined as follows: 1) discrepancies between planning and budgeting documents, 2) reporting of performance which has not run well, 3) human resources which need strengthening, 4) the lack of leadership qualities of SKPD (working units), and 5) the lack of an integrated application systemKeywords: meaning, performance-based budgeting, SIMRAL, system